Phenomena of Online Transportation Mode Choice as an Alternative Public Transport in South of Jakarta - Hasan, Muhammad; Rifai, Andri Irfan; Djamal, Endry Z. (DAS Institute, 2022)
Online transportation has appeared quite attached to our ears in recent years. With increasingly advanced digital technology, many new platforms have emerged, such as Gojek, Grab, and others. This paper aims to find out the public's choice of online transportation in Jakarta amidst increasingly severe traffic jams. The method used in this study was carried out quantitatively by distributing questionnaires to 100 correspondents on social media. As a result, the level of importance of all online transport parameters is considered very important, with an average of 4.27. While the performance value obtained is slightly below 4.25, which means it is still considered satisfactory. So, the gap between performance and interest is manageable, only -0.02.